Beyond dramatic revolutions and grand rebellions - Wendy Willems (Communicare)
In the context of the Zimbabwe crisis of the early 2000s, both popular and academic accounts frequently discussed Zimbabweans as passive victims of their government, hereby suggesting that the extensive efforts of the state to create a ‘patriotic’ citizenry through the cultural project of the Third Chimurenga were largely successful. This article argues that the absence of physical protests in the streets should not be equated with an absence of resistance. By adopting a narrow focus on the forms of resistance associated with dramatic revolutions and grand rebellions, journalists and scholars neglected the everyday forms of resistance - such as popular humour and rumour - by means of which Zimbabweans sought to challenge the state. These nascent forms of resistance could have been drawn upon in a more sustained way by the political opposition and civil society in order to provoke political change.